Pentingnya Pengelolaan Arsip Keuangan Dalam Upaya Kemudahan Temu Kembali Arsip - Elisa Oktavianti; Shinta Arum Silfiana; M Iqbal (Pusat Penelitian dan Pengabdian (P3M) STKIP Majenang, 2026)
This study discusses the importance of financial records management in supporting records retrieval. This topic was chosen because financial records play an essential role in administration, auditing, and decision-making, so they must be managed in an orderly, systematic, and accessible manner. This research used a qualitative approach with a descriptive method through library research. Data were collected by identifying, reviewing, and recording relevant written sources, while data were analyzed using descriptive qualitative analysis. The results show that proper financial records management significantly affects the effectiveness of records retrieval. An organized filing system, clear records classification, the use of classification codes, dynamic records lists, and digitalization support can speed up the retrieval process. In contrast, poorly organized management, limited human resources, and inadequate facilities cause records retrieval to become slow and inefficient. Therefore, systematic financial records management is necessary to ensure the availability of information that is fast, accurate, and reliable in supporting organizational performance.